Impact of legal regulation on elective cesarean sections in a secondary complexity maternity hospital in São Paulo state - Giulia Lopes Corte Mainardi; Vinicius Aniceto; João Vitor Zaniboni de Assumpção; Caio Antonio de Campos Prado; Ana Carolina Tagliatti Zani Mantovi; Elaine Christine Dantas Moisés (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: To evaluate the impact of São Paulo State Law n° 17.137/2019 on the cesarean section rate at a public secondary-level maternity hospital and to analyze predictive factors and complications associated with cesarean under request. This law was enacted to allow pregnant women in São Paulo to request a cesarean section without medical indication. Methods: This retrospective study analyzed medical records of pregnant women ≥ 39 weeks gestation attended at the Ribeirão Preto Women's Health Reference Center (CRSMRP-Mater). Two groups were evaluated: 1,999 patients before the law (July 2018–July 2019) and 3,207 after its implementation (August 2019–July 2021, excluding the suspension period). Descriptive and analytical statistical methods were applied. Results: The overall cesarean rates increased significantly from 23.6% to 27.7% (p < 0.01), with 15,1% of cesareans during the law period being under maternal request (134 patients). A previous cesarean was the only factor significantly associated with electing a new cesarean. Hospital length of stay was significantly longer in the law period (p < 0.01), possibly reflecting the increased cesarean rate. No significant differences were observed in maternal or neonatal complications between cesareans under request and those conducted for medical reasons. Conclusion: São Paulo State Law n°. 17.137/2019 was associated with an increased cesarean rate in CRSMRP-Mater. The findings highlight the need for robust educational approaches and evidence-based obstetric practices to reduce unnecessary elective cesareans.